Assessing organisational learning practices in Small and Medium Scale Enterprises (Smes) in Ghana: A case study of selected Smes at Adum-Kumasi - Anyimadu- Antwi Asor, Akua (2015)
A thesis submitted to the Kwame Nkrumah University of Science and Technology; School of BusinessDepartment of Managerial Science,in fulfillment of the requirement for the award of MASTER OF BUSINESS ADMINISTRATION (HRM OPTION)